2020
DOI: 10.1111/1467-9566.13144
|View full text |Cite
|
Sign up to set email alerts
|

Men, chronic illness and healthwork: accounts from male partners of women with endometriosis

Abstract: Currently dominant in medical discourse, the concept of self-management sees the responsibility for health and illness shift from the state to the individual. However, while this emphasis on individual responsibility and management has burgeoned, the role and status of partners and other family members in the management of chronic illness remains under-theorised. While self-management privileges individual responsibility for the management of chronic illness, the role of partners remains unclear. This paper ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This implies that men often employ ineffective strategies for managing stress. Traditional masculine traits, which emphasize strength and control, condition men to suppress vulnerable emotions like fear and sadness, a habit persisting into adulthood ( 88 ). Additionally, a report found that men more frequently engage in regular exercise compared to women ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that men often employ ineffective strategies for managing stress. Traditional masculine traits, which emphasize strength and control, condition men to suppress vulnerable emotions like fear and sadness, a habit persisting into adulthood ( 88 ). Additionally, a report found that men more frequently engage in regular exercise compared to women ( 89 ).…”
Section: Discussionmentioning
confidence: 99%